2021
DOI: 10.1111/bph.15692
|View full text |Cite
|
Sign up to set email alerts
|

Central histaminergic signalling, neural excitability and epilepsy

Abstract: Epilepsy is a common neurological disorder characterized by repeated and spontaneous epileptic seizures and is not well controlled by current medication. Traditional theory suggests that epilepsy results from an imbalance of excitatory glutamate neurons and inhibitory GABAergic neurons. However, new evidence from clinical and preclinical research suggests that histamine in the CNS plays an important role in the modulation of neural excitability and in the pathogenesis of epilepsy. Many histamine receptor ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 148 publications
(229 reference statements)
0
10
0
Order By: Relevance
“…Accumulating studies have demonstrated that three types of histamine receptors (H 1 R, H 2 R and H 3 R) are found in the LGP of rodents, human and non‐human primate brains (Lozada et al, 2005; Nieto‐Alamilla et al, 2016). Perfusion of GP slices with the selective H 3 R agonist immepip inhibits glutamatergic transmission and reduces the spontaneous firing frequency of rat LGP neurons and ultimately promotes rotational behaviour after the systemic administration of apomorphine in experimental rats (Osorio‐Espinoza et al, 2011; Yang et al, 2022). Moreover, histamine has been reported to activate GP neurons through H 2 R and its associated intracellular G S protein–AC–PKA signalling pathway in brain slices in vitro (Chen et al, 2005; Haas & Panula, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating studies have demonstrated that three types of histamine receptors (H 1 R, H 2 R and H 3 R) are found in the LGP of rodents, human and non‐human primate brains (Lozada et al, 2005; Nieto‐Alamilla et al, 2016). Perfusion of GP slices with the selective H 3 R agonist immepip inhibits glutamatergic transmission and reduces the spontaneous firing frequency of rat LGP neurons and ultimately promotes rotational behaviour after the systemic administration of apomorphine in experimental rats (Osorio‐Espinoza et al, 2011; Yang et al, 2022). Moreover, histamine has been reported to activate GP neurons through H 2 R and its associated intracellular G S protein–AC–PKA signalling pathway in brain slices in vitro (Chen et al, 2005; Haas & Panula, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Although the central histaminergic nervous system originates from the tuberomammillary nucleus (TMN) of the hypothalamus, its fibres extensively project to most regions in the brain, including the basal ganglia (Panula & Nuutinen, 2013; Yang et al, 2022; Zhuang, Li, et al, 2018). Past studies have reported that histamine plays an important role in sleep–wake regulation, learning and memory, food intake, body fluid balance and temperature regulation (Haas et al, 2008; Panula et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, the pathophysiological mechanisms by which antihistamines induce seizures are not fully understood. An experimental study found that H1-receptor knockout mice experienced longer and more seizures than wild-type mice 7 . In addition, the administration of H1-receptor antagonists increased seizure severity and neuronal damage in the septum, thalamus, hippocampus, and retrosplenial granular cortex of kainic acid-treated wild-type mice 7 .…”
Section: Discussionmentioning
confidence: 99%
“…An experimental study found that H1-receptor knockout mice experienced longer and more seizures than wild-type mice 7 . In addition, the administration of H1-receptor antagonists increased seizure severity and neuronal damage in the septum, thalamus, hippocampus, and retrosplenial granular cortex of kainic acid-treated wild-type mice 7 . These findings contribute to the knowledge that the central histaminergic neuronal system is a powerful modulator of brain activity, and that its functional disturbance is related to seizure disorders 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation